Pengadaan Tanah Untuk Kepentingan Umum VS Pelindungan Hak Asasi Manusia : Petani Kalasey Mempertahankan Kebun Terakhir - Ashley Juniare Maria Rengkung; Suparjo, Suparjo (LPPM Universitas Ekasakti Padang, 2024)
Law Number 2 of 2012 concerning Land Acquisition for Development in the Public Interest is the core of the Implementation of Land Acquisition which is basically not free from impacts which should also be regulated in this Law. As land plays an important role in everyday life, it is necessary to pay attention to rights and protection regarding its procurement. Law Number 2 of 2012 is too broad to protect the state's power so that it intersects with human rights provisions such as protecting people's rights. This research uses a statutory research approach and a conceptual approach. This research uses secondary data in the form of primary legal materials, namely statutory regulations and secondary legal materials in the form of books and scientific journals. The results of this research reveal (a) Appropriate land acquisition procedures (b) Public interests are the basis for land acquisition (c) The process of applying for PTUN is related to land acquisition (d) Compensation for losses (e) protection of community rights in land acquisition.